Theory of social capital in an analysis of the role of civil society - Nhac P. (Human and Society, 2017)
according to the author, in the early 19th century, but not until the late twentieth century, the notion of social capital has truly become a scientific term studied in a systematic way. From early explorations of Alexis de Tocqueville, and many other social scientific theorists such as Robert Putnam, Pierre Bourdieu, James Coleman Francis Fukuyama, social studies have made an important part of many classic studies in social sciences as well as curricula in universities.
Keywords: гражданское общество; социальный капитал; social capital; civil society; теория социального капитала; роль гражданского общества; theory of social capital; role of civil society